Risk-Based Capital and Investment Returns of Insurance Companies in Kenya: Moderating Effect of Firm Size - Chache, Willys Obuba; Mwangi, Cyrus Iraya; Nyamute, Winnie; Angima, Caren (European Scientific Journal, ESJ, 2020)
The link between risk-based capital and investment returns remains unclear due to divergence in findings. Mixed findings can be attributed to operationalization of study variables, selection of variables and control variables, the choice of econometric models, and contextual differences which give rise to conceptual, methodological, and contextual gaps. This paper focuses on the moderating effect of firm size on the relationship between RBC and investment returns. Risk-based capital was computed by incorporating market, insurance, credit and operational risk charges. The firm size was measured using gross written premium, while investment returns were measured using investment income ratio. The study population comprised of 63 insurance companies licenced by Insurance Regulatory Authority from 2014 to 2018, where a longitudinal panel design was adopted. Multiple linear regression was used to evaluate the nature of the relationship among variables based on the hypothesis in the study and at a significance level of 5%. The findings confirmed that firm size, both gross written premiums and total assets, had a moderating effect on the relationship between risk-based capital and investment returns. Insurance companies who intend to hold a reasonable risk-based capital so as to ensure stability in times of financial crisis should consider their size either in asset base or the gross premium written. Firms can strive to underwrite more insurance business and increase their asset base in order to safeguard themselves from a one in two-hundred-year crisis and concurrently maximize the investment returns.